Training and Assistance in Recording Financial Reports Using the Buku Warung Application for MSMEs at Condongcatur and Beringharjo Markets - Shindi SS. Lando; Tutut Dewi Astuti (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Financial statements are beneficial for business actors, including MSMEs. From these financial statements, the position and financial condition of the business can be known, so it can be used as an evaluation material in determining the direction of the business or strategies to face competition. The majority of MSMEs in Condongcatur Market and Beringharjo Market still record financial statements manually, which is vulnerable to the risk of losing transaction data/files. This makes the financial statements incomplete. In this digital era, many applications offer ease of recording financial statements for MSMEs, however many have not been able to use them properly due to limited digital knowledge. This activity aims to help overcome these problems by providing training and mentoring for recording MSME financial statements using the Buku Warung application. The method used is a survey, providing material on the importance of financial statements for MSMEs, training and mentoring on using the Buku Warung application, and evaluating the activity. The results show that this activity helps MSMEs record financial statements efficiently and avoid losing transaction data again. Suggestion givens it is hoped that this community service activity will continue to help more MSMEs.